Improving the Suitability of Subject Choices for Students with Hearing Impairments through Digital Media Career Counseling Based on Holland's Theory - Lestari, Prima Harsi Kantun; Dewi Arum Widhiyanti Metra Putri; Ni Ketut Suarni; Nyoman Dantes (Bisma The Journal of Counseling, 2025)
The selection of vocational subjects for students with hearing disabilities should ideally be aligned with their individual interests, potentials, and personality types, as proposed in John Holland’s career theory. However, in practice, many students end up choosing subjects that do not match their personal characteristics due to limited access to structured and informative career guidance services. This study aims to develop and evaluate the effectiveness of a career counseling model based on Holland’s theory, integrated with digital media, in improving the alignment of vocational subject choices among students with hearing disabilities. This Research and Development (R&D) study employed the ADDIE development model and involved five students with hearing disabilities as trial participants. The research instruments included content validation questionnaires, practicality assessments, and evaluations of the appropriateness of vocational subject choices, all of which underwent validity and reliability testing. Data analysis was conducted using the Lawshe validity index (CVR and CVI), descriptive quantitative analysis, N-Gain test, and the Wilcoxon signed-rank test. The results showed that the counseling model had high content validity (CVI = 1), was highly practical (average practicality score of 97.91%), and was significantly effective in improving the appropriateness of vocational subject choices, as evidenced by a high N-Gain score and statistically significant Wilcoxon test results. These findings suggest that integrating digital media with Holland-based counseling is an innovative, effective, and inclusive strategy to support accurate career decision-making among students with hearing disabilities.